FAMOUS WRITERS OF AMERICA - Abdurahmonov T.S; Abdumoʼminova Noila (TADQIQOTLAR, 2025)
Abstract This article includes some general information about well-known writers who mostly contributed to American literature's growth and gained a fame among readers all around the world.